2019
DOI: 10.3390/su11113026
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Collaborative Activities for Sustainable Supply Chain Innovation: An Analysis of the Firm Size Effect

Abstract: This study examines the effects of collaborative and implementation activities on environmental performance for sustainable supply chain management. Specifically, the proposed research investigates the moderating effect of firm size on the effect relationships. The structural equation modeling with AMOS 23.0 was employed to test hypotheses. The results confirm the positive effects of collaborative activities on environmental performance and the positive relationship between collaborative activities and green c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
1
30
0
2
Order By: Relevance
“…The adoption of a proactive environmental management approach also fosters cooperation with key external stakeholders on environmental issues such as waste management or green purchasing [53], or even participation in green supply chains [73]. Cooperation with a wide range of external agents to work on environmental aims is especially critical for the tourism industry, as the competitiveness of its firms is highly dependent on the quality of the natural resources and the welfare of the community living in the tourist destination where they compete [74].…”
Section: Proactive Environmental Management and Environmental Performmentioning
confidence: 99%
See 2 more Smart Citations
“…The adoption of a proactive environmental management approach also fosters cooperation with key external stakeholders on environmental issues such as waste management or green purchasing [53], or even participation in green supply chains [73]. Cooperation with a wide range of external agents to work on environmental aims is especially critical for the tourism industry, as the competitiveness of its firms is highly dependent on the quality of the natural resources and the welfare of the community living in the tourist destination where they compete [74].…”
Section: Proactive Environmental Management and Environmental Performmentioning
confidence: 99%
“…This variable was measured with a seven-point Likert-type scale reflecting managers' perceptions of the firm's level of achievement of environmental objectives (1 = "very low", 2 = "low", 3 = "quite low", 4 = "average", 5 = "quite high", 6 = "high", and 7 = "very high") as compared to competitors in their specific subsector. Specifically, it includes five items adapted from previous studies [96] also validated in recent literature (e.g., [37,71,73]), i.e., 'Reduction in the consumption of materials for service provision', 'Reduction in the energy consumption for service provision', 'Reduction in the time required for service provision', 'Reduction in the environmental impact', and 'Improvement of equipment efficiency'.…”
Section: Dependent Variable Environmental Performance (Envperf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature extensively focused on the broader context of green innovation covering various dimensions of corporate environmental sustainability (Dangelico, Pujari, & Pontrandolfo, 2017; Ester Martínez‐Ros, 2019; Song & Yu, 2018). The increasing demand on environmental compliances from their buyers, reflect a number of customer green orientation (CGO) initiatives, such as customers' request on green vendor certification (Lee, 2019), customer investment in green activities (Caniëls, Gehrsitz, & Semeijn, 2013), and customer green collaborative activities such as customer awareness program and customer green education (Youn, Hong, Yang, & Jungbae Roh, 2012). Previous literature has shown that buyers sharing green expectation with their collaborative partners, can enhance green product innovation (Wong, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A wider scope of the SCM at the strategic level is more relationship-based which emphasizes partnership development with all stakeholders to gain synergy from stronger collaboration [14]. Efficient uses of resources through LM along the whole supply chain can lead to long-term sustainability (i.e., economic, environmental, and social dimensions) [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%